Nginang: Kebiasaan Masyarakat Tradisional Dalam Memelihara Kesehatan Gigi dan Mulut - Sutana, I Gede; Sinarsari, Ni Made; Dwipayana, A.A. Putra (Institut Hindu Dharma Negeri Denpasar, 2021)
The expression of the soul of a traditional society in building its cultural existence is based on an action that is carried out intensely in life, one of which is the habit of nginang. This habit is the habit of traditional people in expressing themselves in social and cultural spaces so as to build the characteristics and identity of the territory. Nginang is a traditional community habit that is generally seen in life in Indonesia, Including Bali for generations. The habit of nginang is an ancestral heritage that is very rare ad almost extinct in Bali. This habit has actually received little attention among young people, although in fact, this habit can be understood to have many benefits, one of which is maintaining healthy teeth and mouth. Practically, nginang ingredients consisting of betel leaf, pinah fruit, whiting, gambier and tobacco have extraordinary benefits because they contain several main compounds such as sesquiterpenes, kavikol, eugenol, cineol, flavonoids, tannins, catechins, and alkaloids.